Giant De Novo Pleomorphic Adenoma Arising from the Parapharyngeal Space - Sang Hwang; Sim Choroomi; Ben McArdle; Ian Jacobson (Case Reports in Otolaryngology, 2013)
Introduction. De novo pleomorphic adenomas in the parapharyngeal space are rare and cause difficulties in its surgical management. We report the largest de novo pleomorphic adenoma arising from the parapharyngeal space and discuss its surgical management. Presentation of Case. A 34-year-old male presented with a giant de novo pleomorphic adenoma arising from the parapharyngeal space, which was initially misdiagnosed as an impacted wisdom tooth. Measuring 8.4×6.5×3.9 cm in size and weighing 87.3 g, this is the largest primary salivary gland tumour arising de novo from the parapharyngeal space reported in the literature, presenting challenges in its surgical management. Discussion. Parapharyngeal space tumours cause nonspecific symptoms and may be difficult to diagnose, which can allow the tumours to become very large and cause obstructive and compressive symptoms in an anatomically difficult area. A combined trans-cervical and trans-oral approach can be used to safely perform an en bloc resection. Conclusion. We report the diagnosis and surgical management of the largest pleomorphic adenoma arising de novo from the parapharyngeal space reported in the literature.